Prevention and control of enteric swine diseases - R M Phillips; N V Anderson (Kansas Agricultural Experiment Station Research Reports, 1979)
Work on colibacillosis has been concentrated on isolating and identifying enterotoxigenic E. coli from specimens submitted to the Veterinary Diagnostic Laboratory. Strains of enterotoxigenic E. coli isolated in the laboratory were sent to veterinary practitioners to use in producing of autogenous vaccines for producers to prevent neonatal diarrhea. Of 1,179 E. coli isolated from clinical specimens and tested for enterotoxin production, more than 22 percent of these isolates were disease-producing enterotoxigenic strains. These enterotoxigenic E. coli were sent to 136 veterinary practitioners for use in autogenous vaccines. The diagnostic laboratory also serves as a center for storing these vaccine strains.; Swine Day, Manhattan, KS, November 8, 1979
Keywords: Swine day; 1979; Kansas Agricultural Experiment Station contribution; no. 80-136-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 371; Swine; Enteric swine diseases; E.coli